Regulation of BPJS Employment Contributions for Workers Other than State Organisers who Receive Wages Below the Regency / City Minimum Wage - Sarah Adhibah Suprayitno; Mahendra Wardhana (NOVUM : JURNAL HUKUM, 2025)
This research explores the regulatory framework of BPJS Employment tariffs, focusing on workers whose wages fall below the Regency/City Minimum Wage (UMK). The study aims to examine how BPJS Employment regulates contribution payments between employers and workers earning below the UMK, as well as to analyze the legal implications arising from discrepancies in reported wages during BPJS registration. The research adopts a normative juridical method, grounded in the logic of legal science from a normative perspective. It views the law as a structured system of norms, principles, and statutory rules used to resolve legal issues. The study identifies a normative void in existing regulations, stemming from the unclear articulation of the wage components subject to BPJS contributions. To address this, the research applies legal reasoning by analogy. It concludes that in the absence of an official wage suspension, employers must comply with Article 32 paragraph (2) of Presidential Regulation Number 64 of 2020, which mandates adherence to the prevailing minimum wage standard. Moreover, companies that fail to register their employees with BPJS Employment are subject to administrative sanctions, including formal warnings, cessation of business operations, or revocation of business licenses. The study recommends regulatory clarification on wage components used in calculating contributions and stricter enforcement mechanisms to ensure compliance, particularly for vulnerable low-wage workers.